Analisis Tindak Tutur Direktif dalam Film Sejuta Sayang Untuknya Sutradara Herwin Novianto dan Skenario Pembelajarannya di Kelas XI SMA - Siti Adila Putri Kurnia; Achmad Yuhdi (Universitas Muhammadiyah Mataram, 2022)
This study aims to determine the directive speech act, to find out the directive speech act in the film Sejuta Sayang Untuknya, and to find out the scenario of learning directive speech acts in the film Sejuta Sayang Untuknya in class XI of SMA. The subject of this research is the film Sejuta Sayang Untuknya, directed by Herwin Novianto. This research focuses on directive speech acts and speech forms in the film Sejuta Sayang Untuknya by director Herwin Novianto. The method used in this research is descriptive qualitative. Data collection was carried out using the free-of-charge listening technique (SBLC) and note-taking techniques. From the results of the study, it was found that there were six directive speech acts, including eighteen command directive speech acts, ten request directive speech acts, six invitation directive speech acts, twelve advice directive speech acts, nine speech criticism directive speech acts, and four directive speech acts. ban. Scenario of learning in class XI SMA in the dialogue film Sejuta Sayang Untuknya, director Herwin Novianto uses discovery learning learning methods based on KD 3.19 Analyzing the content and language of the drama or film that is read or watched.